Structural, optical and thermal properties of Er3+-Ag codoped bio-silicate borotellurite glass - Hamza, A. M.; Halimah, M. K.; Muhammad, F. D.; Chan, K. T.; Usman, A.; Faznny, Mohd Fudzi; Zaitizila, I.; Tafida, R. A. (Elsevier Science, Ltd., 2019)
In this paper, thermal, structural and spectroscopic properties of Er3+-Ag+ codoped bio-silicate borotellurite [{[(TeO2)0.8 (B2O3)0.2]0.8 (SiO2)0.2}0.99 (Ag2O)0.01]1-y (Er2O3)y where y = 0.05 glass are studied. The thermal and structural studies have been conducted using differential scanning calorimetry (DSC) and X-ray diffraction (XRD) respectively so as to confirm the nature of the glass sample. The Fourier transform infrared (FTIR) has revealed the basic structural units of the glass system. Ultra violet visible (UV–Vis) spectrometer was used to measure the absorption spectrum and was analysed using Judd-Ofelt (J-O) and McCumber theory. Other important parameters such as radiative lifetime, branching ratio and transition probability are also determined from the analysis. The peak emission cross section discovered from McCumber theory is 4.9 × 10−21 cm2 . This value is larger than that of phosphate, silicate and tellurite glasses. The gain band width and figure of merit are used to evaluate the application of the glass in optical amplification and solid state laser.